Portal venous gas in intestinal malrotation with mild midgut volvulus - Ryuichiro Hirose; Hiroki Kai; Kaori Inatomi; Tsuyoshi Iwanaka; Naomi Morishima; Momotoshi Ikeda; Reiko Masaki; Akinori Iwasaki (Surgical Case Reports)
Abstract Background Portal venous gas has been considered as a radiological sign requiring urgent operative intervention; however, the reports concerning portal venous gas associated with favorable outcome are recently increasing. Case presentation We describe a 9-month-old boy with acute onset high fever and vomiting. The ultrasonography demonstrated micro-gas bubbles continuously floating in the intrahepatic portal vein. Contrast-enhanced CT, performed 1 h later from echography, revealed a whirlpool sign suggesting an intestinal malrotation with midgut volvulus, but with no signs of residual intrahepatic gas. Operative findings showed a mild volvulus with neither congestion nor ischemic change of the twisted bowel. Detorsion and Ladd’s procedure were completed laparoscopically. Conclusions Transient portal venous gas bubbles may be generated even in the mild intestinal volvulus with no bowel ischemia. Ultrasonography can be a sensitive detector to visualize such small amounts of gas.